Immersive journalism as a new digital media communication platform (Herald of Journalism, 2018)
For the first time theory and practice of journalism, issues of immersive journalism are considered in Kazakhstan, which is now an actual trend in foreign media production.The purpose of the article is to provide journalists and researchers with knowledge about future media that will exist in a “multi-platform” environment, in which, along with traditional ones, digital me- dia, including immersive journalism, will take their place. It allows you to “deeply immerse” in a virtual environment, create effect of presence with audio and video accompaniment.The research methodology includes a critically-comparative analysis of virtual reality study models and the use of immersive journalism, an analysis of the experience of foreign universities and media organizations. The author believes that the theoretical and practical material of the research will help to create a new course at the Faculty of Journalism, and will become the basis for its implementation in the educational process. The value of the conducted practical and theoretical research will make it possible to make a significant contribution to the development of the educational environment at a high scien- tific and technological level. The practical significance of the results of the work on the example of the experience of such publications as The Guardian, The New York Times, CNN, as well as the pioneer in the field of immersive journalism Nonni De la Pe a, will reveal the potential role and importance of im- mersive journalism in the practice of Kazakh journalism, will affect the educational process of journalism education, as well as create new perspectives for journalism practitioners.Key words: immersion journalism, virtual reality, 360 video, new education technologies, digital media.
Keywords: Key words: mass media, TV program, media culture, national traditions, culture, information content.